Show some Methods for Computing the Drazin Inverse - Kareema alrabbae; Ahlam alhadi (Surman Journal of Science and Technology, 2025)
The Drazin inverse of a matrix A is a matrix that satisfies the condition = . In general, Drazin inverses are exist and unique where A is singular or even rectangular, while if A is non-singular square matrix, then reduces to the usual inverse of A and denoted by .